Reduction of Methylglyoxal-Induced Glycation by Pyridoxamine Improves Adipose Tissue Microvascular Lesions - Tiago Rodrigues; Paulo Matafome; Daniela Santos-Silva; Cristina Sena; Raquel Seiça (Journal of Diabetes Research)
Background and Aims. Adipose tissue dysfunction results from many factors, including glycation-induced microvascular damages. We tested the usefulness of inhibiting methylglyoxal-induced glycation to adipose tissue microvasculature in this work, using the antioxidant and dicarbonyl scavenger drug pyridoxamine. Methods. A group of Wistar rats was treated daily with methylglyoxal (MG, 75 mg/Kg/day, 8 weeks). Half of this group was treated with pyridoxamine in the following 4 weeks (Pyr) (100 mg/Kg/day) and the other half did not have any further treatment (MG). A group of Wistar rats without MG treatment was used as control (C). Results. MG group showed decreased HDL cholesterol and increased plasma free fatty acids levels, what was reverted by pyridoxamine. MG also caused an increase of tissue CEL levels (glycation marker), as well as increased staining of PAS and Masson Trichrome-positive components. Pyridoxamine led to CEL and TGF-β levels similar to those observed in control rats and inhibited the accumulation of PAS and Masson Trichrome-positive components. MG caused a decrease of Bcl-2/Bax ratio (marker of apoptosis) and vWF staining (microvascular marker), what was partially reverted by the treatment with pyridoxamine. Conclusions. Preventing methylglyoxal-induced accumulation of glycated and fibrotic materials using pyridoxamine improves the microvascular lesions of the adipose tissue.